2019
DOI: 10.1093/mnras/stz340
|View full text |Cite
|
Sign up to set email alerts
|

Evaporating the Milky Way halo and its satellites with inelastic self-interacting dark matter

Abstract: Self-interacting dark matter provides a promising alternative for the cold dark matter paradigm to solve potential small-scale galaxy formation problems. Nearly all self-interacting dark matter simulations so far have considered only elastic collisions. Here we present simulations of a galactic halo within a generic inelastic model using a novel numerical implementation in the AREPO code to study arbitrary multi-state inelastic dark matter scenarios. For this model we find that inelastic self-interactions can:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 101 publications
4
77
0
Order By: Relevance
“…[252]), and in which scattering between the excited and ground states can result in energy injection at the centre of dark matter haloes thus altering their structure. Only until very recently have these models began to be explored with simulations [166,253].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[252]), and in which scattering between the excited and ground states can result in energy injection at the centre of dark matter haloes thus altering their structure. Only until very recently have these models began to be explored with simulations [166,253].…”
Section: Discussionmentioning
confidence: 99%
“…This discussion refers strictly to elastic self-scattering. If collisions are inelastic, then the energy released needs to be taken into account and, in fact, it could prevent the gravothermal collapse; see [166].…”
Section: The Structural Properties Of Dark Matter Haloesmentioning
confidence: 99%
“…Recently, it has been shown that the self-interacting dark matter (SIDM) model [7,8] can explain diverse rotation curves of field spiral galaxies [9][10][11], a serious challenge for CDM [12,13]. In SIDM, dark matter collisions thermalize the inner halo over the cosmological timescale [14][15][16][17][18] and correlate dark matter and baryon distributions [19][20][21][22][23][24][25], in accord with observations of spiral galaxies in the field. SIDM may also provide a solution to puzzles associated with dwarf spheroidal galaxies (dSphs) in the Milky Way (MW), e.g., the most massive subhalos predicted in CDM are too massive to host the bright MW dSphs [26,27].…”
mentioning
confidence: 81%
“…For example, DM with non-zero free streaming velocities suppresses the matter power spectrum and delays halo formation, resulting in a lower number density of virialized structures and less concentrated DM haloes (Lovell et al 2014;Menci et al 2018). Moreover, strong DM self-interactions, through kinematic thermalization, tie the DM distributions to the baryonic ones (Kaplinghat et al 2014;Elbert et al 2018;Sameie et al 2018) such that it potentially reduces the tension in some of the small-scale puzzles (Vogelsberger et al 2012;Zavala et al 2013;Rocha et al 2013;Peter et al 2013; osame001@ucr.edu † NASA MIRO FIELDS Fellow * Hellman Fellow Kamada et al 2017;Creasey et al 2017;Robertson et al 2018a,b;Vogelsberger et al 2019;Valli & Yu 2018;Ren et al 2018). DM could also be coupled to dark radiation such that this extra relativistic component could potentially explain the tension in the measurements of H 0 from local and CMB observations, and also, through damping the power spectrum via dark acoustic oscillations (DAO), reduce the tension in σ 8 measurements and possibly the missing satellites problem (e.g.…”
Section: Introductionmentioning
confidence: 99%